A theoretical–experimental study of KSr2Nb(3-x)TaxO10 (x = 0,1,2) systems as photocatalysts - Medeiros, Rayssa B.; Silva, Jeronimo F.; Menezes de Oliveira, Andre L.; Sambrano, Julio R. [UNESP]; Albuquerque, Anderson R.; Maia, Ary S. (Elsevier, 2023)
Understanding the influence of structural changes arising from electronic characteristics is a significant challenge in novel material development. The Nb(V) and Ta(V) cations are pertinent due to their similar ionic radii across various coordinations. Layered perovskites (KSr2Nb(3-x)TaxO10, where x = 0,1, and 2) were synthesized using the solid-state method. These compounds were characterized employing experimental techniques and subjected to photocatalytic testing in a model reaction. Density Functional Theory simulations were conducted, confirming experimental data accuracy and prediction reliability. Evaluation of intra and inter-octahedral distortion and charge carrier effective masses were correlated with experimental outcomes. Remarkably, substituting Nb with Ta increased photocatalytic activity, suggesting a promising avenue for tailoring material properties.
Keywords: DFT; Effective mass of charge carriers; Layered perovskites; Octahedrons distortion; Photocatalysis